Retrospective evaluation of premenopausal hormone-sensitive breast cancer patients treated with adjuvant gonadotropin-releasing hormone analogue: Anatolian Society of Medical Oncology (ASMO) study - DANE, FAYSAL (WILEY, 2018)
AimThe goal of this study is to evaluate possible factors affecting the survival of patients treated with gonadotropin-releasing hormone (GnRH) analogues. MethodsDemographic characteristics, treatment modalities, overall survival (OS) and the possible factors affecting the survival a total of 554 premenopausal breast cancer patients in Turkey evaluated retrospectively. ResultsThe median duration of GnRH analogues use was 2213.6 (range, 1-87) months. Patients were divided into three groups according to the duration of GNRH analogues use; 4-12 months (Group A), 13-24 months (Group B) and 25 months (Group C). Overall, 530 patients were analyzed; 23.2%, 45.8%, 30.9% of the patients were in Group A, B and C, respectively. The median follow-up duration was 34 +/- 30.3 (range, 4-188) months. The OS in patients 35 years of age was found to be significantly longer than that of patients >35 years of age in Group B (log rank, P = 0.023). The disease-free survival of the patients in Group A was significantly shorter than that of patients in Group C (log rank, P = 0.003). The OS of Group A patients was significantly shorter in comparison to that of Group B and Group C patients (log rank, P = 0.000) and the OS of Group B patients was significantly shorter than Group C (log rank, P = 0,000). ConclusionThere is currently no definite data on the optimal duration of GnRH analogues use. One of the important results of this study that will provide an insight to the future studies is the improvement gained in OS by the increase in the duration of GnRH analogues use.
Keywords: breast cancer; medical oncology; pharmacy; OVARIAN SUPPRESSION; WOMEN; THERAPY; GOSERELIN; CHEMOTHERAPY; TRIAL